Analisis Desain PLTB Horizontal 0,3 kW Berbasis QBlade di Tangerang - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Tom Rizkon Uzarni Paradongan (JTM : JURNAL TEKNIK MESIN, 2026)
The low utilization of small-scale wind energy in urban residential areas requires a technical design approach that considers local wind speed, blade geometry, rotor configuration, and generator suitability. This paper analyzes a 0.3 kW horizontal-axis wind power design for the Grand Duta residential area, Tangerang, using the QBlade simulation approach. The design uses a three-blade horizontal rotor with a 2 m rotor radius, NACA 4412 airfoil, and taperless blade concept. Wind data were obtained from BMKG and direct anemometer measurements, then simplified into design parameters. The local average wind speed used in the design was approximately 4 m/s, with cut-in, rated, and cut-out references of 2.8 m/s, 8.0 m/s, and 12.0 m/s, respectively. The selected blade design used NACA 4412 with an optimum angle of attack of 6 degrees, Cl/Cd of 133.5, and Cl of 1.12. The QBlade simulation at 0 degree pitch showed that the rotor produced 252.676 W at 4 m/s and 300 rpm, while the maximum simulated power reached 2324 W at 20 m/s. At 6 degree pitch, the maximum simulated power reached 2837 W. The results indicate that the design is technically feasible as a small horizontal-axis wind turbine concept, although further prototype testing is required to validate structural strength, generator matching, and field performance.